SOUND TRANSMISSION LOSS OF A DOUBLE-LEAF PARTITION WITH MICRO-PERFORATED PLATE INSERTION UNDER DIFFUSE FIELD INCIDENCE - Putra, Azma; Ismail, Ahmad Yusuf; Ayob, Md Razali (Universiti Malaysia Pahang, 2013)
In noise control applications, a double-leaf partition has been applied widely as a lightweight structure for noise insulation, such as in car doors, train bodies, and aircraft fuselages. Unfortunately, the insulation performance deteriorates significantly at mass-air-mass resonance due to coupling between the panels and the air in the gap. This paper investigates the effect of a micro-perforated panel (MPP), inserted in the conventional double-panel partition, on sound transmission loss at troublesome resonant frequencies. It is found that the transmission loss improves at this resonance if the MPP is located at a distance of less than half that of the air gap. A mathematical model is derived for the diffuse field incidence of acoustic loading.